A Comparative Study on In-vivo Biocompatibility of Four Endodontic Sealers - Rania M. Khashaba; Mervet M. Moussa (New Frontiers in Medicine and Medical Research Vol. 11, 2021)
The aim of this study was to compare the biocompatibility of two new calcium phosphate – based root canal sealers (CPC-I, CPC-II) with a commercially available zinc oxide eugenol based-sealer [Pulp canal sealer EWT (PCS EWT)] and Sealapex after implantation in the subcutaneous tissue of rats. Sterile polyethylene tubes were filled with the test materials. The tubes were implanted in the dorsum of male rats and after 1, 2, 4 and 8 weeks, the animals were killed, obtaining 5 specimens for each sealer. Empty tubes were used as negative control. Inflammation, major cell types, and fibrous connective tissue thickness next to each inserted sample were all measured. At week one, all sealers induced similar inflammatory reactions in the animals’ connective tissue, with most specimens displaying a moderate to severe chronic inflammatory response. After 2 weeks, CPC-II and (PCS EWT) showed a severe inflammatory reaction with presence of acute inflammatory cells, while CPC-I and Sealapex induced mild and moderate inflammatory reactions respectively. After 4 weeks, connective tissue in contact with CPC-I and Sealapex was more organized, while the tissue close to CPC-II and (PCS EWT) showed a moderate inflammatory reaction and had similar results to each other. After 8 weeks, mild inflammatory reactions were observed for CPC-I, (PCS EWT), and Seal apex. CPC-I induced the lowest inflammatory response at all evaluation periods, only CPC-II did not show a decrease in the inflammatory reaction over time. CPC-I sealer can be assigned a favorable biocompatibility level based on the study’s histological findings.